Numerical simulation of electromagnetic induction responses of 2D resistive structures as an aid for interpretation of archaeological data - Martinelli, Hilda Patricia (2004)
A Frequency-domain Electromagnetic Induction System was used to characterize an archaeological site in South Patagonia. This method involves the measurement of the change in mutual impedance between a pair of moving coils. The data are usually interpreted directly from the In-Phase and Quadrature components, and sometimes also by performing a 1D or in some particular cases 2D inversions. Most of the applications of this method point to the detection of metals and other conductive bodies. Notwithstanding, we have found in a previous paper that good resolution can be obtained for detecting also resistive structures. In the present paper, we analyzed the sensitivity of the method to characterize a structural feature that was present at the archaeological site: two adobe walls with tile deposits between them, both with a clear resistive electrical signature. Using the 2D forward modeling code introduced in that paper, we performed numerical simulations of the In-Phase and Quadrature components of the response of the above mentioned buried structure. The results were then used to interpret the data acquired at the site. The archaeological structure and the soil environment were modeled using information from excavations as well as from geoelectrical data; then, we calculated the synthetic responses using the 2D forward code and these results were compared to data. The good correlation obtained confirmed us that these resistive structures present a characteristic signature, which can be distinguished in the response patterns.